Bisnis perikanan alat tangkap sero di Desa Rumba-Rumba Kecamatan Kolono Timur Kabupaten Konawe Selatan - Wahyuni; Piliana, Wa Ode; Arami, Hasnia; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aimed to determine the fishery business of guiding barrier trap in Rumba-Rumba Village, East Kolono District, South Konawe Regency. The research was carried out in November 2022 at Rumba-Rumba Village, East Kolono District, South Konawe Regency. Observation data were obtained through interviews of 11 fishermen. Data analysis was quantitative and descriptive analysis, costs, revenues and profits. The results showed that the average number of sero fishing trips in Rumba-Rumba Village was 1 (one) trip/day with the species of fish caught consisting of siganids, snapper and trevally. The total cost of sero fishermen were ranged from IDR437,118/month to IDR87,583/month or with an average of IDR560,385/month. Marketing activities for sero fishermen in Rumba-Rumba Village were carried out directly and indirectly. Total revenue from share fishermen was averages of IDR1,168,636/month or around IDR940,000/month to IDR1,430,000/month. Profits of share fishermen average IDR608,251/month or around IDR440,125/month to IDR820,861/month. The conclusion of this study concluded that the shareholding business in Rumba-Rumba Vilage based on business studyes was profitable.